Evaluation of Antihypertension Drugs on Patients Diabetes Mellitus in RSI Sultan Agung Semarang 2016 - Dian Oktianti; Nurul Fitria Dewi; Meiji Pujiawati (Faculty of Pharmacy, Universitas Gadjah Mada)
More than 50% of patients with type 2 diabetes mellitus are associated with hypertension. Uncontrolled blood pressure in patients with type 2 diabetes mellitus correlated with the onset of cardiovascular and cerebrovascular complications. Therefore, proper blood pressure management is needed to delay and prevent complications. Selection of appropriate antihypertensive drugs along with appropriate doses is one way to inhibit the possibility of complications. The purpose of this study is to know about the accuracy of the use of antihypertensive drugs and doses used. This research is a descriptive and observational retrospective research. The subjects of the study were 88 patients with diabetes mellitus with accompanying hypertension. Data taken include antihypertensive, antidiabetes mellitus, laboratory data. The data obtained are then analyzed descriptively using JNC edition 8 and DIH 2015. The results showed that there were 88 samples meeting the inclusion and exclusion criteria. The commonly used single antihypertensive group is Angiotensin Receptor Blocker (ARB) of 56.09%, and antihypertensive combination is Angiotensin Receptor Blocker (ARB) - Calsium Chanel Blocker (CCB) of 65.95%. Based on the results of analysis, the results obtained for the right drug and the patient is 98.86% and for the accuracy of the dose obtained 97.72%.